Electromagnetic Wave Theory and Applications - Kong, Jin Au; Ding, Kung-Hau; Shin, Robert T.; Yang, Ying-Ching Eric; del Frate, Fabio; Sun, Liguo; Hsu, Chih-Chien; Martinez, Angel R.; Shih, Shih-en; Thomassier, Vincent; Wang, Li-Fang; Zhang, Yan; et al. (Research Laboratory of Electronics (RLE) at the Massachusetts Institute of Technology (MIT), 1996)
Contains table of contents for Section 3, reports on nine research projects and a list of publications. National Aeronautics and Space Administration Contract 958461 U.S. Navy - Office of Naval Research Grant N00014-92-J-1616 University of California/Jet Propulsion Laboratory Contract 960408 U.S. Army - Corps of Engineers/Cold Regions Research and Engineering Laboratory Contract DACA89-95-K-0014 Mitsubishi Corporation U.S. Navy - Office of Naval Research Agreement N00014-92-J-4098 Federal Aviation Administration DEMACO Joint Services Electronics Program Grant DAAHO4-95-1-0038